2020
DOI: 10.46423/izujed.752446
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between in-Service Teachers’ Mindset Types and Their Efficacy Beliefs in Instructional Strategies

Abstract: Mindset is the belief of whether people's abilities can be improved or not. It has been an essential phenomenon in education, and the value of this concept cannot be ignored in teachers' educational career. Teachers' mindset plays a pivotal role in learner achievement and building up self-esteem. On the other hand, there has not been much research that examines teachers' mindset and teacher efficacy in instructional strategies. Thus, this study aims to investigate the relationship between in-service teachers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The married teachers' LS level is higher than that of single teachers. This finding is consistent other studies (Yılmaz and Aslan, 2013;Ünal et al 2001;Linn et al 1985). These results support the research results.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The married teachers' LS level is higher than that of single teachers. This finding is consistent other studies (Yılmaz and Aslan, 2013;Ünal et al 2001;Linn et al 1985). These results support the research results.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
“…In female teachers, LS is reported to be higher than that of male teachers. Yılmaz and Aslan (2013), Aysan and Bozkurt's (2004) studies on teachers, Ünal et al (2001)'s study on physicians and the findings obtained from Yıldız (2016)'s study on university students are similar to the results of the research. In addition, the findings were found in the literature that there is no significant difference in LS in different genders (Özkul and Cömert, 2018;Özkara et al 2015;Hintikka et al 2001;Hampton and Marshal, 2000;Yıldırım, 2019;Elçi et al 2019;Walker and Kono, 2018), and also there were also studies in favor of it (Bai et al, 2018;Oerbeck, 2019).…”
Section: Conclusion and Discussionsupporting
confidence: 63%
“…Çetinkaya (2004) emphasized that marital status affects life satisfaction and concluded that marital status has a positive effect on life satisfaction. Yılmaz and Aslan (2013) examined teachers' life satisfaction and loneliness at work and found that life satisfaction showed a significant difference according to gender variable. Botha and Booysen (2013) examined the relationship between marital status and life satisfaction in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The composite mean of 3.31 shows that the teachers' sense of efficacy in terms of instructional strategies is at a very high level. Yilmaz (2020) found that teachers who have a growth mindset use instructional strategies more effectively than those with a fixed mindset. Moreover, when teachers adopt growth mindsets, it enhances their teacher efficacy in instructional strategies.…”
Section: Composite Mean 331 Very High Levelmentioning
confidence: 96%